Alkaloids from Piper nigrum and Piper betle - Lim, Chyi Meei; Ee, Gwendoline Cheng Lian; Rahmani, Mawardi; Bong, Choon Fah Joseph (Universiti Putra Malaysia Press, 2009)
An investigation, on the roots of Piper nigrum and the aerial parts of Piper betle, has yielded several alkaloids. The dried root sample of Piper nigrum was extracted using various solvents in increasing polarity. The dried aerial part of Piper betle was extracted using the Soxhlet extraction method. The alkaloids isolated were pellitorine(1), (E)-1-[3',4'- (Methylenedioxy)cinnamoyl]piperidine(2), piperine(3), piperolactam D(4), cepharadione A(5), and 2,4-tetradecadienoic acid isobutyl amide(6). These compounds were isolated using chromatographic methods, while the elucidation of the structures was carried out using MS, IR and NMR techniques. The extracts of Piper nigrum and Piper betle were also tested for cytotoxicity activities. This is the first report on (E)-1-[3',4'-(Methylenedioxy)cinnamoyl] piperidine(2) from Piper nigrum as a natural product.